Governance of Diversity Between Social Dynamics and Conflicts in Multicultural Cities. A Selected Survey on Historical Bibliography - Ercole Sori; Renato Sansa (Fondazione Eni Enrico Mattei (FEEM), 2005)
This paper is an excursus on multiculturalism from a historical perspective. It ranges from the encounters of different cultures in ancient times, through the Middle Ages, the Reformation and Counter-Reformation period up to the present times. It describes the peculiarity of the solutions adopted, juridical or social, formal or informal. Although it is difficult to classify the various attitudes towards foreigners, a decisive distinction should be made between modern history and previous times. Until the 19th century the number of migrants was significant in a historical perspective, but limited in absolute terms. May this fact have helped the hosting institutions to encourage a favourable policy towards foreign settlements? Another distinction must be made between high qualified migration and humble and unskilled workers. Cities histories are full of discriminatory measures towards local immigrants from villages who swelled the ranks of urban outcasts. Finally, it seems clear that the category of multiculturalism, as a premise for the successful integration of foreigners can only be applied with precautions to historical examples. The challenge of the clash of cultures was tackled differently in past societies, without necessarily meaning that those societies were racist or xenophobic. Successful examples of integration and development with the contribution of diversity in the past could involve exclusion and discrimination apparently unacceptable nowadays.
Keywords: 330; Social dynamics; Conflicts; Multicultural cities; Diversities